Generation and mutational analysis of a transgenic mouse model of human SRY. Issue 3 (28th December 2021) - Thomson, Ella; Zhao, Liang; Chen, Yen‐Shan; Longmuss, Enya; Ng, Ee Ting; Sreenivasan, Rajini; Croft, Brittany; Song, Xin; Sinclair, Andrew; Weiss, Michael; Koopman, Peter; Pelosi, Emanuele
Abstract: SRY is the Y‐chromosomal gene that determines male sex development in humans and most other mammals. After three decades of study, we still lack a detailed understanding of which domains of the SRY protein are required to engage the pathway of gene activity leading to testis development. Some insight has been gained from the study of genetic variations underlying differences/disorders of sex determination (DSD), but the lack of a system of experimentally generating SRY mutations and studying their consequences in vivo has limited progress in the field. To address this issue, we generated a mouse model carrying a human SRY transgene able to drive testis determination in XX mice. Using CRISPR‐Cas9 gene editing, we generated novel genetic modifications in each of SRY 's three domains (N‐terminal, HMG box, and C‐terminal) and performed a detailed analysis of their molecular and cellular effects on embryonic testis development. Our results provide new functional insights unique to human SRY and present a versatile and powerful system in which to functionally analyze variations of SRY including known and novel pathogenic variants found in DSD.